Design and implementation of informatization for unified management of stroke rehabilitation in urban multi-level hospitals - Huang, Lihua; Jiang, Lan; Xu, Yiming; Ma, Yanhong (Frontiers in Neuroscience, 2023)
Background With the aging of the population, the prevalence and incidence of stroke in China are increasing every year. China advocates the establishment of a three-level medical service system for stroke rehabilitation, but it lacks uniform information management among all levels of medical institutions. Objective To achieve unified management of stroke patient rehabilitation in multilevel hospitals in the region through informatization construction. Methods The need for informatization of three-level stroke rehabilitation management was analyzed. Then, network connections were established, and a common rehabilitation information management system (RIMS) was developed for all levels of hospitals to enable daily stroke rehabilitation management, inter-hospitals referral, and remote video consultation. Finally, the impact on the efficiency of daily rehabilitation work, the functioning and satisfaction of stroke patients were investigated after implementing the three-level rehabilitation network. Results One year after implementation, 338 two-way referrals and 56 remote consultations were completed using RIMS. The stroke RIMS improved the efficiency of doctors’ orders, reduced therapists’ time to write medical documents, simplified statistical analysis of data and made referrals and remote consultations more convenient compared to the traditional model. The curative effect of stroke patients managed by RIMS is better than that of traditional management. Patient satisfaction with rehabilitation services in the region has increased. Conclusion The three-level stroke rehabilitation informatization has enabled the unified management of stroke rehabilitation in multilevel hospitals in the region. The developed RIMS improved the efficiency of daily work, improved the clinical outcomes of stroke patients, and increased patient satisfaction.